Evidence-based guidelines for the pharmacological treatment of postmenopausal osteoporosis: a consensus document by the Belgian Bone Club - Body, J.-J. (Springer-Verlag, 2010)
Several drugs are available for the management of postmenopausal osteoporosis. This may, in daily practice, confuse the clinician. This manuscript offers an evidence-based update of previous treatment guidelines, with a critical assessment of the currently available efficacy data on all new chemical entities which were granted a marketing authorization. Osteoporosis is widely recognized as a major public health concern. The availability of new therapeutic agents makes clinical decision-making in osteoporosis more complex. Nation-specific guidelines are needed to take into consideration the specificities of each and every health care environment. The present manuscript is the result of a National Consensus, based on a systematic review and a critical appraisal of the currently available literature. It offers an evidence-based update of previous treatment guidelines, with the aim of providing clinicians with an unbiased assessment of osteoporosis treatment effect.